이러닝에서 사회성, 사용용이성, 유용성, 즐거움이 수용의향에 미치는 영향 연구 -확장된 기술수용모델 관점 - 이종만; Lee, Jong-Man (한국콘텐츠학회 논문지, 12(4), 2012)
The purpose of this paper is to examine factors influencing e-Learning acceptance intention through extended Technology Acceptance Model(TAM) applying TAM, the motivation theory, and the social response theory. To do this, this paper proposes and analyzes a theoretical model consisting of factors such as perceived sociability, perceived ease of use, perceived usefulness, perceived enjoyment, and e-Learning acceptance intention. Our findings are revealed as following: First, perceived usefulness and perceived enjoyment have positive effects on e-Learning acceptance intention. Second, perceived ease of use has positive effects on determinants of e-Learning acceptance intention. Third, perceived sociability not only has direct influence on e-Learning acceptance intention but also has indirect influence carried by perceived usefulness. 본 연구의 목적은 기술수용모델, 동기이론, 사회적 반응 이론을 적용한 확장된 기술수용모델 관점에서 이러닝 수용의향에 영향을 미치는 요인들을 살펴보는 것이다. 이를 위하여 지각된 사회성, 지각된 사용용이성, 지각된 유용성, 지각된 즐거움, 그리고 이러닝 수용의향으로 구성된 이론모형을 개발하고 분석하였다. 분석 결과를 요약하면 첫째, 지각된 유용성과 지각된 즐거움은 모두 이러닝 수용의향에 직접적인 영향을 미치는 결정요인으로 밝혀졌다. 둘째, 지각된 사용용이성은 이러닝 수용의향 결정요인인 지각된 유용성과 지각된 즐거움에 긍정적인 영향을 미치는 요인으로 나타났다. 셋째, 지각된 사회성은 이러닝 수용의향에 직접적인 영향을 미칠 뿐만 아니라 지각된 유용성을 매개로한 간접적인 영향도 미치는 것으로 밝혀졌다.